2020
DOI: 10.1186/s13063-020-04396-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality, scope and reporting standards of randomised controlled trials in Irish Health Research: an observational study

Abstract: Background: Despite efforts to improve the accuracy and transparency of the design, conduct, and reporting of randomised controlled trials (RCTs), deficiencies remain. Such deficiencies contribute to significant, avoidable waste of health research investment and impede reproducibility. This study aimed to synthesise and critically analyse changes over time in the conduct and reporting of internationally published evidence on patient and/or population health-oriented RCTs conducted in one country. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…Despite the widespread endorsement of CTR globally, CTR in FFC remains suboptimal, with no registration or, in many cases, unknown existence of the protocol itself (24%). Our findings are consistent with previous studies that reported protocols were not fully registered [ 16 , 17 , 18 , 19 , 20 , 21 ]. Gopal et al [ 18 ] concluded that unregistered trials were more likely to report favorable findings than were registered trials (89% vs. 64%, relative risk = 1.38, 95% confidence interval = 1.20–1.58; p = 0.004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the widespread endorsement of CTR globally, CTR in FFC remains suboptimal, with no registration or, in many cases, unknown existence of the protocol itself (24%). Our findings are consistent with previous studies that reported protocols were not fully registered [ 16 , 17 , 18 , 19 , 20 , 21 ]. Gopal et al [ 18 ] concluded that unregistered trials were more likely to report favorable findings than were registered trials (89% vs. 64%, relative risk = 1.38, 95% confidence interval = 1.20–1.58; p = 0.004).…”
Section: Discussionsupporting
confidence: 93%
“…There are also few registrations in the fields of surgery [ 19 ] and addiction [ 20 ] or for trials in a single country’s health research [ 21 ], which could be because the journal’s regulation did not require registration as a prerequisite for submitting papers. The same might be inferred in the field of nutrition, so journals other than ICMJE member journals are also considered to have an urgent need to register protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate reporting of dual-registered trials on EUCTR is a prevalent issue [ 46 ], which may in part reflect the register’s reliance on sponsors to manually enter study results onto the EudraCT database. Suboptimal completion of RCT protocols and results may lead to overestimates of trial activity [ 47 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, The Lancet published the article series "Increasing Value and Reducing Waste" that describes underlying problems and provides possible solutions (3)(4)(5). Even though the first version of the CONSORT statement was published more than 20 years ago, quality of reporting remains suboptimal (6,7). But even if adherence to reporting guidelines would be perfect, essential information often remains unclear for certain aspects (5).…”
Section: Why Share Data?mentioning
confidence: 99%
“…• Manipulations to decrease precision: Too much precision bears the risk of making entries linkable to persons. Possible methods to decrease precision include relative time in the course of the study instead of precise dates and times 6 , rounding of continuous data, grouping and aggregation (categorization), introducing random noise (jittering, perturbation), setting certain values to missing (suppression), data swapping, resampling or subsampling.…”
Section: Detailed Specification Of Required Data Processing Stepsmentioning
confidence: 99%